Periods and well-being: A focus group study to discuss how menstruation affects the well-being of women aged 18–40 - Caroline Musulin; Natania Yeshitila; Joyce Harper (Women's Health)
Background: Menstruation is a central experience in women’s lives throughout their reproductive years, and in some cases, it can significantly impact quality of life. Investigating women’s attitudes towards their periods, how it may affect their well-being and identifying areas for improved education and support is crucial. Objectives: To explore women’s attitudes towards their periods, the impact on their well-being, their management strategies, and their experiences with menstrual education, along with suggestions for improvement. Design: Qualitative analysis of online focus group discussions. Methods: Participants were divided into two groups according to their age. Five focus groups were conducted for each group. Group 1 included 26 women aged 18–25 and group 2 included 29 women aged 26–40. Women were recruited online via social media to participate in a focus group to discuss their menstrual experiences. The discussions were transcribed and analysed using content analysis to identify key themes and commonalities. Results: Participants expressed mixed attitudes towards their periods, often highlighting the inconvenience to their daily lives, whereas some noted a sense of community among women. Overall menstruation negatively impacted various aspects of their well-being, from physical health to personal relationships. Participants employed a range of management strategies and overwhelmingly felt that their education inadequately prepared them for menstruation. Stigma emerged as a pervasive theme, influencing their attitudes, well-being, management approaches, and educational experiences. Conclusion: This study underscores the significant impact of menstruation on women’s well-being and highlights the urgent need for improved menstrual education and support. Recommendations include providing early, gender-inclusive education and ensuring there is support for those with difficult periods. The importance of support networks in managing menstrual health is also emphasised.